The Impact of Artificial Intelligence (AI) on the Scope of Accountancy: Difficulties and Challenges in a Literature Review - Rusgowanto, Fransisca Hanita (Tinta Emas Institute, 2024)
The rapid advancement of Artificial Intelligence (AI) technologies has permeated various industries, ushering in transformative changes. One such sector experiencing significant shifts is accountancy. This paper presents a systematic literature review to discern the impact of AI on the domain of accountancy, aiming to unveil its repercussions, challenges, and difficulties. The review draws from a vast array of academic journals, white papers, industry reports, and conference proceedings. The results indicate that while AI streamlines tasks like data processing and forecasting, leading to enhanced efficiency and accuracy, it also brings about potential challenges. These challenges include the demand for new skill sets, fears of job displacement, ethical considerations, and the requirement for updated regulatory frameworks. However, a noteworthy observation during this review was the complexities and challenges in carrying out a systematic review itself, given the rapid technological advancements and diverse perspectives in the existing literature. Inconsistencies in terminologies, overlapping scopes, and the multifaceted nature of AI applications in accountancy further complicated the process. This paper offers a dual contribution: shedding light on the implications of AI in accountancy and providing insights into the intricacies faced while conducting a systematic literature review in a dynamic field.